2020
DOI: 10.1016/j.jesf.2019.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeine ingestion on free-throw performance in college basketball players

Abstract: BackgroundIt is currently unclear whether pre-exercise caffeine ingestion can improve free-throw shooting performance, a vital skill in basketball. The purpose of this study was to investigate the effects of caffeine on free-throw shooting performance in college-aged basketball players.MethodsTwelve males (23.1 ± 1.9 years; 180.1 ± 8.8 cm; 77.1 ± 12.4 kg) and six females (22.0 ± 1.3 years; 169.4 ± 8.9 cm; 67.0 ± 11.1 kg) who competed at the college level ingested 6 mg per kg of body mass of (a) caffeine or (b)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 36 publications
0
34
0
1
Order By: Relevance
“…Five studies included both males and females and analyzed them together, presenting pooled data. We collected mean and error values only for the female group after contacting the corresponding authors of two of the studies [14,35]. We did not include two studies [36,37] that presented both sexes because the corresponding authors confirmed that they involved the same participants and tests that were presented in the following two studies that were included in the meta-analysis [32,38].…”
Section: Meta-analysesmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies included both males and females and analyzed them together, presenting pooled data. We collected mean and error values only for the female group after contacting the corresponding authors of two of the studies [14,35]. We did not include two studies [36,37] that presented both sexes because the corresponding authors confirmed that they involved the same participants and tests that were presented in the following two studies that were included in the meta-analysis [32,38].…”
Section: Meta-analysesmentioning
confidence: 99%
“…The individual PEDro quality scores ranged from 8 to 10, being excellent in 15 studies and good in 3 studies (Supplementary Material: Table S2). Three crossover trials did not meet the requirements related to therapist and assessor blinding [33,35,40], and the study performed by Fernandez-Campos et al [41] did not include drop-outs in the analysis.…”
Section: Quality Assessment and Risk Of Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Concentration affects the ability to shoot because when a player is shooting requires a high concentration so that when the player is shooting at the goal is not affected by disturbances both from outside or inside the player (Nakano et al, 2020;Tan, Burns, Pan, & Kong, 2020), meaning that the player who has a high concentration will be easy for him to do the shooting as desired. This applies to the findings of the research results.…”
Section: Resultsmentioning
confidence: 99%